2012
DOI: 10.5581/1516-8484.20120049
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease: acute clinical manifestations in early childhood and molecular characteristics in a group of children in Rio de Janeiro

Abstract: ObjectivesTo describe clinical events of sickle cell disease and the correlation with β-globin haplotypes and α-thalassemia in under 6-year-old children.MethodsA retrospective study was conducted of under 6-year-old children from the neonatal screening program in Rio de Janeiro. Forty-eight male and 48 female children were enrolled in this study, 79 with sickle cell anemia and 17 with hemoglobin SC. The mean age was 29.9 (standard deviation = 20.9) months, 62 (16.2 ± 8.6) were aged between 0-3 years old and 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
7
6
0
1
Order By: Relevance
“…Brazilian studies also found a correlation between SCA clinical manifestations, Hb Fand the beta S-globin haplotype ( 8 , 9 , 13 , 19 , 25 , 29 , 30 ) , including more vaso-occlusive crises ( 9 , 29 ) , more infections ( 9 ) and slower growth ( 29 ) in the CAR haplotype, high levels of Hb F ( 13 , 19 , 25 ) and nitrites in the BEN haplotype ( 19 ) , and increased risk of cerebro vascular disease (CVD) in children with the Bantu/atypical haplotype compared to other beta S-globin haplotypes ( 30 ) . Patients with the CAR/BEN haplotype had less painful crises compared to the other haplotypes ( 22 ) .…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Brazilian studies also found a correlation between SCA clinical manifestations, Hb Fand the beta S-globin haplotype ( 8 , 9 , 13 , 19 , 25 , 29 , 30 ) , including more vaso-occlusive crises ( 9 , 29 ) , more infections ( 9 ) and slower growth ( 29 ) in the CAR haplotype, high levels of Hb F ( 13 , 19 , 25 ) and nitrites in the BEN haplotype ( 19 ) , and increased risk of cerebro vascular disease (CVD) in children with the Bantu/atypical haplotype compared to other beta S-globin haplotypes ( 30 ) . Patients with the CAR/BEN haplotype had less painful crises compared to the other haplotypes ( 22 ) .…”
mentioning
confidence: 82%
“…Patients with the CAR/BEN haplotype had less painful crises compared to the other haplotypes ( 22 ) . Trials have shown no correlations between co-inheritance with alpha-thalassemia and clinical symptoms ( 8 , 9 , 22 ) , however it may be associated with less infections ( 13 ) or with repeated acute pain crises ( 29 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from genotype and allele frequencies are shown in Table 1. The high frequencies of Bantu and Benin haplotypesdemonstrate the influence of Western and South-Central African on the evolution of the Brazilian population (6) . We identified atypical haplotypes which may have originated due togenetic mechanisms such as gene conversions and the intense miscegenation between ethnicgroups that inhabit Rio de Janeiro State and Brazil.…”
mentioning
confidence: 99%
“…Este evento requer intervenção imediata, pois pode evoluir para choque hipovolêmico. A esplenectomia, que representou 17,24% de todas as causas de internação, é o tratamento terapêutico para esta complicação clínica, indicada após duas crises de sequestração esplênica ou após o primeiro episódio grave (15,10,21) . A palidez cutânea acometendo quase a totalidade dos pacientes com AF, geralmente está associada à icterícia, dispneia, astenia e intolerância a atividade física.…”
Section: Discussionunclassified